Chelating Ligand-Mediated Hydrothermal Synthesis of Samarium Orthovanadate with Decavanadate as Vanadium Source - Quanguo Li; Wenli Zuo; Feng Li (The Scientific World Journal)
A new ethylenediaminetetraacetic acid- (EDTA-) mediated hydrothermal route to prepare chrysanthemum-shaped samarium orthovanadate (SmVO4) nanocrystals with decavanadate (K6V10O28·9H2O) as vanadium source has been developed. The present hydrothermal approach is simple and reproducible and employs a relatively mild reaction temperature. The EDTA, pH value, and temperature of the reaction systems play important roles in determining the morphologies and growth process of the SmVO4 products. The products have been characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT-IR), photoluminescence spectra (PL), and UV-Vis spectroscopy.